Stability of Family Values in the Context of Digital Transformation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Digital transformation has a profound impact on various aspects of society, including family values. The development of information and communication technologies, the acceleration of the globalization process and the popularization of social networks occupy an important place in the processes of formation, stability and transformation of family relations. The article also talks about the stability and transformation of family values in the context of digital transformation.